Pro Express.js - Mardan, Azat (Expert's voice in Web development., 2014)
Pro Express.js is for the reader who wants to quickly get up-to-speed with Express.js, the flexible Node.js framework. Author Azat Mardan clearly explains how to start developing with Express.js with a basic 'Hello World', and then delves into a deep API reference, before looking at common and abstract development problems. Lastly, you will learn how to build a series of real-world apps in order to cement your knowledge. In order to get the best from this book, you will be familiar with Node.js scripts and able to install packages using npm. In the deep API reference, each aspect of the Express.js API is explained clearly with a simple exercise to demonstrate its usage. This includes configuration, settings and environments; different middleware and its uses; templating engines; extracting parameters and routing; request and response; error handling; and running an app. In the next part you'll delve into abstraction, streams, authentication, multithreading, Socket.io, security, and more complex modules. You will also learn about smaller frameworks built using Express.js, such as Sails.js, and Derby. Finally you'll build real-world apps including a REST API, Todo App, and Instagram gallery. Express.js is used by a range of well-known companies such as MySpace and Storify, and it's becoming more and more likely that it'll be a required skill for new developers. With this book you can skip learning via complicated documentation, and get the information from a developer who's been using Express.js for long enough to explain things well. Add Pro Express.js to your library today.